The Guatemalan construction characterizaton of the perceived risk by managers of suffering work accidents - Hernández-Arriaza, Francisco Arturo; Pérez-Alonso, José; Gómez-Galán, Marta; Salata, Ferdinando; Callejón-Ferre, Ángel Jesús (Journal of Civil Engineering and Management, 2020)
The construction industry is considered one of the highest risk production sectors, even more so in developing countries such as Guatemala. A characterization has been carried out on the perception of Guatemalan construction company managers regarding, the risk of accidents exist for the different activities they perform. The characterization has been carried out on a representative sample of the business population via a questionnaire. A preliminary data analysis was performed followed by a Descriptive and a Multiple Correspondence Analysis. Companies are characterized as “mediumsize” companies, with an average of 81.1 construction workers per year and average annual turnover of 1.29 million euros. 4 clusters of construction activities occur with similar accident weightings. Companies in Cluster 1 are associated to the variables grouped with a Low risk weighting, with a medium to high number of on-site workers and with a turnover of more than 100,000 euros. In contrast, those in Cluster 2 are associated with the variables grouped as having a Medium risk weighting, with a low number of on-site workers and a turnover of less than 100,000 euros. The companies in Cluster 3 are only associated with High risk weighted. And those of Cluster 4 with Not applicable risk-weighting variables.